2000
DOI: 10.1021/la9912601
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Thermodynamics of Surfactants at the CO2−Water Interface

Abstract: Measurements of the interfacial tension γ at the water-CO2 interface with the surfactant perfluoropolyetherCOO-NH4 + (M w = 2500) are utilized to determine the surfactant interfacial area, surface pressure vs area, critical microemulsion concentration, and the thermodynamic properties of microemulsion formation. The measurements were made at equilibrium vs surfactant concentration with a tandem variable-volume pendant drop tensiometer from 25 to 65 °C at a constant CO2 density of 0.842 g·mL-1. The experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
137
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(146 citation statements)
references
References 58 publications
8
137
0
1
Order By: Relevance
“…In recent years, microemulsions with supercritical CO 2 as the continuous phase have been studied extensively. [29][30][31][32][33][34][35] It is well known that some compressed gases, such as CO 2 , are quite soluble in many organic solvents and they can reduce the solvent strengths to such a degree that the solutes can be precipitated. [36][37][38] Our previous work showed that compressed CO 2 and ethylene can increase the solubilization capacity of water in sodium bis-2-ethylhexylsulfosuccinate (AOT) and Triton X-100 reverse-micellar systems at suitable pressures because the gases can insert into the interfacial region to enhance the rigidity of the interface layers and reduce the interdroplet attraction.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, microemulsions with supercritical CO 2 as the continuous phase have been studied extensively. [29][30][31][32][33][34][35] It is well known that some compressed gases, such as CO 2 , are quite soluble in many organic solvents and they can reduce the solvent strengths to such a degree that the solutes can be precipitated. [36][37][38] Our previous work showed that compressed CO 2 and ethylene can increase the solubilization capacity of water in sodium bis-2-ethylhexylsulfosuccinate (AOT) and Triton X-100 reverse-micellar systems at suitable pressures because the gases can insert into the interfacial region to enhance the rigidity of the interface layers and reduce the interdroplet attraction.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of studies involving W/C emulsions (10)(11)(12) and W/C microemulsions (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) have been reported recently. Based on observations of the volume fractions of the upper and lower phases after shear, emulsions with a C/W morphology have been reported (25,26).…”
Section: Introductionmentioning
confidence: 99%
“…6. As shown in the figure, both the higher and lower phase transition pressures at 3 wt% of TMN-3 concentration were lower than those at 1 wt%, which would be caused by the effects of differences in surface properties that arise from the difference in TMN-3 concentration in scCO 2 , because it is reported that the interfacial tension between water and scCO 2 decreased with increasing concentration of surfactant for several types of surfactants [18,32,27]. On the other hand, the maximum value of W 0 obtained at 3 wt% of TMN-3 was lower than that obtained at 1 wt% of TMN-3, as shown in Fig.…”
Section: Scco 2 + Tmn-3 + Water Systemmentioning
confidence: 90%
“…In addition to investigations of engineering applications utilizing both W/CO 2 microemulsion and macroemulsion, basic studies from the viewpoint of thermodynamic stability and interfacial behavior were reported by Johnston et al [15][16][17][18][19][20][21][22][23]. Moreover, a phase diagram is also important for the development of novel processes utilizing W/CO 2 microemulsion and macroemulsion, therefore, the phase behaviors of the scCO 2 + surfactant + water systems were also measured.…”
Section: Introductionmentioning
confidence: 99%